CMTM10 investigation on upper limb and lower back muscles activities during sedentary work. - Md Dawal, S.Z. (2010)

(untitled)
The objective of this study is to investigate the upper limb and lower back muscles activities while performing a repetitive task in two different work area boundaries during sedentary work. Subjects consisted of 10 males (age mean = 27.7) and 10 females (age mean = 27.5) with no history of musculoskeletal injury or back problem at the time of participation. All of them are right hand dominance and performed same repetitive task in the near and in the far boundary work area in sedentary position. Surface electromyography (EMG) signals were recorded from the Right and Left Levator Scapulae, Right and Left Upper Trapezius, Right and Left Anterior Deltoid and Right and Left Erector Spinae. The results indicated that muscles activities increased significantly when performing work in the far boundary work area. The muscle activity in the far boundary work area is averagely 17% greater than in the near boundary work area. The most active muscle is the Erector Spinae. Females showed higher %MVC compared to males with average of 1.62 %MVC in near and 2.0 %MVC in far boundary work area. The result from independent sample t-test showed that the muscular activities are also affected by the gender differences. Keywords: Muscle Activity, Prolonged Sitting, Electromyography